Structural and functional studies on human oxygenases - Islam, S (2017)
The work described in this thesis focused on 2-oxoacid-dependent oxygenase enzymes. Most of the work focused on iron- and 2-oxoglutarate (2OG)-dependent oxygenases including JMJD6 and JMJD5, which are human enzymes of unassigned or controversial functions. Work was carried out also on human 4-hydroxyphenylpyruvate dioxygenase (HPPD), which is a structurally distinct 2-oxoacid oxygenase involved in tyrosine catabolism. The work involved protein purification, biophysical analysis, substrate screening, and inhibitor profiling. Chapter 1 gives an introduction to 2OG oxygenases summarizing their functions, structures, and mechanisms. Chapters 2-6 describe functional assignment, structural, and inhibition studies on JMJD6, which has been previously reported as phosphatidylserine receptor (PTDSR), as an N-methyl arginine demethylase, and as a lysyl-hydroxylase. The overall results using peptide as substrate support the assignment of JMJD6 as lysyl C-5 hydroxylase. Crystallographic studies reveal JMJD6 to be more similar to the JmjC hydroxylases than demethylases. JMJD6 was found to act on sequences of substrates including splicing regulatory (SR) proteins, such as U2AF65 (U2 small nuclear ribonucleoprotein auxiliary factor 65 kDa subunit), LUC7L2 (putative RNA binding protein luc 7-like 2), and CROP (cisplatin resistance-associated overexpressed protein). It also acted on sequences of substrates including p53, estrogen receptor α (ERα), and von Hippel-Lindau (VHL). There was no evidence for JMJD6-catalysed demethylation activity either on N-methyl arginine- or N-methyl lysine-residues. Studies on the non-catalytic domain of JMJD6 reveal a role of the polyserine domain in regulating catalytic activity. Structural and kinetic studies reveal how JMJD6 is inhibited by the structural analogues of 2OG. Chapters 7-8 describe crystallographic and other studies on JMJD5, which has been assigned as an arginine residue C-3 hydroxylase, and N-methyl lysine demethylase. The results support the assignment of JMJD5 as a hydroxylase rather than demethylase and will enable the development of selective JMJD5 inhibitors. Chapter 9 describes studies on human HPPD from crystallographic and inhibition perspectives. The results highlight common features at the active sites of the two classes of human 2-oxoacid oxygenases. Overall, the results inform on the functions of JMJD6 and JMJD5 as hydroxylases and will enable the development of selective inhibitors of them for use in target validation and the assignment of their biological roles.